Not a "chosen elitism": privilege and volunteerism at AWARE. - Tham, Janice Jia Yi. (2012)
Using the Association of Women for Action and Research (AWARE) as a case study, this study reveals how localised ideas about privilege are woven into the rationalisations that are given by volunteers to explain their participation in the women's rights group. It is hoped that such a case study will shed light on some of the discursive mechanisms that are at play that influence participation not just in the women’s rights campaign but also civil society in Singapore.